An Epidemiological Study on the Assessment of Cardiovascular Health Status Among Medical Doctors In Lumbini Province, Nepal - Sudhir Kumar Shah, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Cardiovascular diseases remain the leading contributor to global mortality, accounting for approximately 17.9 million deaths annually, which constitutes nearly one-third of all deaths worldwide. In order to reduce the burden of CVD, we first need to assess cardiovascular health status of population. The health status of doctors is critically important, as optimal physical and metabolic well-being is essential for maintaining effective clinical performance in demanding healthcare settings. MATERIAL AND METHODS In this cross sectional study, Cardiovascular health status of 354 sampled doctor’s population of Lumbini Province were assessed using pre-designed and pre-tested semi structured questionnaire from August 2022 to December 2022. Samples were taken from doctor’s population using non probability purposive sampling technique. Blood pressure, Blood glucose, Blood cholesterol, Body height and weight were measured using standard guidelines. RESULTS Mean age of study population was 37.89 ±7.70 years. Hypertension was seen among 22% of doctor’s population. Among doctors, 58% had ideal level of fasting blood sugar and 77% had ideal level of cholesterol level. The present study showed substantially high prevalence of obesity BMI > 23(65%) among doctors population. Married were more obese (65%), hypertensive (26%) and diabetics (14%) compared to unmarried. CONCLUSION The study demonstrates a considerable burden of major cardiovascular risk factors—including hypertension, diabetes mellitus, dyslipidaemias, and increased body mass index—among doctors, warranting serious attention. Healthy lifestyle measures might reduce burden of CVD which could be evaluated in future research.